Development of HIF-1 inhibitors for cancer therapy - Onnis, Barbara (John Wiley & Sons, Ltd, 2009)
Intratumour hypoxia has long been considered a driving force of tumour progression and a negative prognostic factor in human cancers. The discovery of hypoxia inducible factors (HIFs), which mediate transcriptional responses to changes in oxygen levels, has renewed enthusiasm for the discovery and development of targeted therapies exploiting the hypoxic tumour microenvironment. In spite of an ever increasing number of putative small molecule inhibitors of HIF, only few progress through pre-clinical and early clinical development. In this review, we will focus primarily on: (1) HIF inhibitors that have been more recently described and (2) small molecules targeting HIF that are being tested in early clinical trials or that are already approved for use in patients. A rigorous ‘validation’ of HIF targeted therapies in relevant pre-clinical models and eventually in pharmacodynamic-based early clinical trials is essential for ‘credentialing’ HIF-1 as a legitimate target that can be pharmacologically modulated in cancer patients.